Interiority in Everyday Space: A Dialogue between Materiality and Occupation - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (Interiority, 2019)
Everyday space is a setting where ordinary acts, activities and events take place. It is interesting to examine closely how interiority is defined, understood and manifested in everyday space as a way to understand the inhabitation of the interior. The interiority of everyday space is defined not only by occupation but also through materiality. This issue of Interiority presents articles that address the relationships between interior materiality and different perceptual constructs and experiences of architectural space as inherent in the occupation of the everyday space.